Fast high-fidelity geometric quantum control with quantum brachistochrones - Yang Dong; Ce Feng; Yu Zheng; Xiang-Dong Chen; Guang-Can Guo; Fang-Wen Sun (Physical Review Research, 2021)
We experimentally demonstrate fast and high-fidelity geometric control of a quantum system with the brachistochrone method on hybrid spin registers in diamond. Based on the time-optimal universal geometric control, single geometric gates with fidelities over 99.2% on the spin state of the nitrogen-vacancy center are realized with average durations shortened by 21.5% compared with the conventional geometric method. The fidelity of the fast geometric two-qubit gate exceeds 96.5% on the hybrid spin registers. With the fast and high-fidelity universal set of geometric gates available, we implement a quantum entanglement-enhanced phase estimation algorithm and demonstrate the Heisenberg quantum limit of phase estimation at room temperature. Hence our results show that high-fidelity quantum control based on a fast geometric route will be a versatile tool for broad applications of quantum information processing in practice.